Hubungan Antaragama dalam al-Qur’an: Ayat Kalimatun Sawā’ dalam Perspektif Maqāṣid al-Qur’ān Sa‘īd al-Nursī: Interreligious Relationship in the Koran: Chapters on Common Ground in the Perspective of Sa’id al-Nursi’s Maqasid al-Qur’an - Muhammad Abdul Aziz (Besari: Journal of Social and Cultural Studies, 2025)
Neglecting the exclusive and inclusive aspects of the teaching of Islam is among the obstacles to carrying out fruitful interreligious relations. By limiting the research to the verse of kalimatun sawā’ (common ground) coupled with two methods, i.e., the textual and comparative, the present research aims to explore such two dimensions within the context of the concept of maqāṣid al-Qur'ān proposed by Sa‘īd al-Nursī in his Rasa'il al-Nur. This research concluded that within al-Nursī’s four articles of maqāṣid al-Qur'ān, i.e., monotheism (tawhīd), prophethood (nubuwwah), the day of resurrection (ḥashr), and justice (‘adl), the first three are exclusive binding only on Muslims while the last one is inclusive that applies universally. In the context of kalimatun sawā’ as a case study, it is revealed two available options that serve as the common ground, i.e., the call for authentic monotheism (indicated by e.g., allā na‘buda illā Allāh) and, if this fails, the submission to God (biannā muslimūn) as to the truth of their own beliefs so as to create interreligious tolerance for the sake of materializing social justice. The first option, which consists of monotheism and prophethood, is considered exclusive while the second, which comprises justice and the Last Day, is inclusive and exclusive.